CEO Reputation and Earnings Quality* - Francis, Jennifer; Huang, Allen H.; Rajgopal, Shivaram; Zang, Amy Y. (Contemporary Accounting Research, 2008)
We examine the association between chief executive officer (CEO) reputation (proxied by the extent of press coverage) and the quality of the firm's earnings (proxied by two accruals-based measures). We test three explanations for an association between these constructs: the efficient contracting hypothesis suggests that reputed CEOs are associated with good earnings quality, while the rent extraction and matching explanations argue that reputed CEOs are associated with poor earnings quality. Using a simultaneous equations system to capture the endogeneity of the constructs, we find (consistent with the rent extraction and matching arguments) that more reputed CEOs are associated with poorer earnings quality than are less reputed CEOs. Further tests find little support for the rent extraction hypothesis. We conclude that the reason more reputed CEOs are associated with poor earnings quality firms is that such firms require more talented managers and, therefore, employ more reputed CEOs. © CAAA.